Cryptococcal Meningitis: Challenges Faced in the Management of a Patient with Cryptococcoma - Priyaadarshini Urjan Mohan; Anupma Jyoti Kindo; SMH Waseem (Journal of Clinical and Diagnostic Research)
Cryptococcus is a genus of opportunistic fungal pathogens that have garnered significant attention in the medical community due to their ability to cause life-threatening infections, particularly in immunocompromised individuals. Cryptococcosis is a fungal infection that can present as an acute, subacute, or chronic infection. Cryptococcus neoformans are basidiomycetous encapsulated yeasts classified into five serotypes based on their capsule. The primary mode of infection is through the inhalation of basidiospores or small, poorly encapsulated yeasts. Cryptococcus neoformans is ubiquitous in the environment, often recovered from eucalyptus trees and bird droppings. This infection typically presents as meningoencephalitis in Human Immunodeficiency Virus (HIV) patients, while in immunocompetent individuals, the infection can be subclinical, manifesting as small granulomatous disease in the lungs without dissemination. The principal symptoms include meningitis, fever and intracranial hypertension. Additionally, altered mental status, seizures, visual changes and focal neurological deficits may arise. Diagnosis relies on the identification of encapsulated yeasts in the cerebrospinal fluid using India ink staining, which has a sensitivity of 50% in immunocompetent individuals. Biopsies of the lungs, skin, bone marrow, brain and other organs may also be conducted, offering higher sensitivity than the former method. The preferred treatment involves a combination of amphotericin B and 5-flucytosine during the induction phase to reduce the fungal load, followed by oral fluconazole in the maintenance phase. In contrast, cerebral cryptococcomas necessitate a longer treatment duration with additional antifungals. The low clinical suspicion of Cryptococcosis often leads to a delayed diagnosis of the infection. Early diagnosis and treatment are crucial for patient survival. Here, a case of Cryptococcaemia in an immunocompetent patient is reported.